ダイ 1 カイ キョクチ セツエイ コウガク シンポジウム ノ ガイヨウ - 楠, 宏; クスノキ, コウ; Kusunoki, Kou (1985)
P(論文) The first Symposium on Polar Logistics sponsored by the National Institute of Polar Research was held on March 16–17, 1984. Giving an emphasis on the logistics problems of the Japanese Antarctic Research Expedition, 20 papers are presented coverring the topics on transportation (6 papers), ice engineering (3 papers), energy (3 papers), buildings (4 papers), and Antarctic provisions (4 papers). The present volume contains 13 papers and one abstract, and late papers will be published in the following volume. departmental bulletin paper